Evaluasi Kerusakan Jalan Soekarno-Hatta STA 09+000-STA 14+000 Kota Balikpapan - Wahyu Yusuf Rio; Fatmawati Fatmawati (Ridwan Institute, 2021)
In this study, a survey of road damage condition with location at km 9 to km 14 (STA 9+00 - STA 14+00) with the aim of knowing the condition of road damage and its handling using Bina Marga and Pavement Condition Index methods. Based on the analysis of Bina Marga method, the level of road damage in STA 9+00-STA 14+00 has an area of 941.12m2, while the highest priority is 5.2 in STA 12+000 -STA 13+000 and the value of road conditions is 6.8. While from the analysis by PCI method obtained the results of the index of pavement conditions are very low with a value of PCI 14 ie at STA 12+850 to STA 12+900 with a category of very bad damage. From the results of road damage assessment, it is necessary to carry out routine maintenance and make repairs in the form of fillings, surface maintenance and crack closures can be used as recommendations for road repairs. From the results of the assessment of road conditions on the soekarno-hatta road section STA 9+000-STA 14+000 Balikpapan city obtained the value of the condition of pavement that suffered damage and must get priority handlersganan first namely STA 13+300 to STA 13+350 obtained pci value 14 which means in very bad condition (very poor), STA 12+8 50 to STA 12+900 obtained PCI value 14 which means in very poor condition, STA 10+250 to STA 10+300 obtained PCI value 42 which means in bad condition (poor), STA 10+600 to STA 10+650 obtained PCI value 31 which means in bad condition (poor).